SOAL MATEMATIKA MODEL PISA: ALTERNATIF MATERI PROGRAM PENGAYAAN - DEWANTARA, ANDI HARPENI (DIDAKTIKA, 2018)
In a learning process, each students’ has different level of capability in mastering the teaching materials. For those who belong to the fast learner group and are able to achieve mastery learning earlier, ideally they need an additional learning activities to develop their skills more optimally. One of such learning activities is commonly known as the enrichment programs. Then, one of the learning challenges that can be applied in this enrichment program is proposing problem solving tasks to foster students' high order thinking skills. Based on the characteristics, it is revealed that PISA problems or PISA-like tasks has characteristics that are very in accordance with the characteristics of the rocemmenced enrichment problems. So that is why PISA problems or PISA-like tasks could be highly regarded as the enrichment tasks for students who have achieved early learning completeness. PISA mathematics problems or PISA-like mathematics tasks is expected to be able to optimize students 'mathematical literacy skills through activation of basic mathematical abilities, which in turn can help the success of enrichment programs in developing students' skills more optimally.